Vertical variation of lead, copper and manganese in core sediments collected from Tanjung Lumpur mangrove forest, Pahang, Malaysia - Yunus, Kamaruzzaman; Mohd Yusuf, Nurulnadia; Mohamad Shazili, Noor Azhar; Saad, Shahbudin; Bidai, Joseph (Penerbit UKM, 2011)
Two core sediment samples collected from Tanjung Lumpur mangrove forest were analysed for lead, copper and manganese using the sensitive Inductively Coupled Plasma-Mass Spectrometry (ICP-MS). The average concentrations of Pb, Cu, and Mn in core samples were 36.28±7.04 μg/g dry weights, 50.17±5.84 μg/g dry weights, and 110.41±14.48 μg/g dry weights, respectively. From the calculated enrichment factors (EF), only Mn was considered to be predominantly terrigeneous in origin, while Pb and Cu have slightly higher EF values which were related to anthropogenic input.